IMPLEMENTASI KEBIJAKAN MERDEKA BELAJAR DALAM UPAYA MENINGKATKAN MUTU PENDIDIKAN DI INDONESIA - Seif Malik Aziz (Bajang Institute, 2023)
This research will discuss abouth what is meant by freedom to learn, what are the aims of the freedom to learn policy and what are the implications of the policy of freedom to learn in efforts to improve the quality of education in Indonesia. The research method used is a descriptive qualitative research method using literature study. Research data will be analyzed descriptively based on theories and new findings resulting from literature review. The research results reveal that freedom to learn is the freedom for education (schools, teachers and students) to innovate, be independent and creative. The aim of independent learning is so that teachers, students and parents can have a happy atmosphere. Some of the implications of the independent learning policy in an effort to improve the quality of education include; Student-oriented learning, teacher commitment, curriculum management and learning processes